1971
DOI: 10.2135/cropsci1971.0011183x001100050052x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Seed Size in Chickpeas (Cicer Arietinum L.)1

Abstract: Two chickpea (Cicer arietinum L.) pure lines, one having small seeds and another with large seeds, were crossed reciprocally. Parents, F1, and F2 generations were grown in a field study to determine the inheritance of seed size. The results showed that large seeds were partially dominant to small seeds with at least eight pairs of genes controlling seed size. Broad sense heritability was estimated to be 81%. No maternal effects were observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Polygenic control of seed weight is common among grain legumes, such as chickpea (Niknejad et al, 1971), broad bean (Cubero, 1984), and common bean (Motto et al, 1978). High heritability estimates of seed weight were recorded for chickpea Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polygenic control of seed weight is common among grain legumes, such as chickpea (Niknejad et al, 1971), broad bean (Cubero, 1984), and common bean (Motto et al, 1978). High heritability estimates of seed weight were recorded for chickpea Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…as well as in the Middle American common bean (Phaseolus vulgaris L.). In chickpea, small seed size was found to be dominant in Desi x Kabuli crosses (Smithson et al, 1985), while polygenic control of seed size and partial dominance of large seed size were found by Niknejad et al (1971). A polygenic system governs seed shape and size in faba beans (Cubero, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in chickpea showed low (Sandha & Chandra, 1969) as well as high (Niknejad et al, 1971;Kumar & Singh, 1995) estimates of heritability for seed size. Small seed size was found dominant over large one (Athwal & Sandha, 1967;Smithson et al, 1985;Kumar & Singh 1995;Malhotra et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…However, there are reports suggesting reverse to be true as well (Niknejad et al, 1971). Additive gene action has been reported to be predominant for seed size inheritance (Malhotra & Singh, 1989;Singh et al, 1992;Singh et al, 1993;Kumar & Singh, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation